Through my eyes - Bridges, Ruby (New York : Scholastic, 1999)
Ruby Bridges recounts the story of her involvement, as a six-year-old, in the integration of her school in New Orleans in 1960.
Keywords: Bridges, Ruby -- Juvenile literature; School integration -- Louisiana, New Orleans -- Juvenile literature